Array - Fitriana, Lysa Nur Azizah (Language Horizon: Journal of Language Studies, 2023)
The study of politeness strategies is important because communication with others needs to use politeness strategies, and a president should speak politely as a state leader. This study aims to reveal the President's politeness and political diplomacy strategies. The research subject is Joe Biden conducting a press conference at the G20 Summit in Bali, Indonesia. Brown and Levinson's 1987 theory is the main theory of this research. This study uses a qualitative descriptive method where the data is taken from YouTube channel videos, and the researcher becomes the instrument to explain the data. It was found in this study that Joe Biden used 16 politeness strategy data, consisting of 9 positive politeness strategy data, 4 negative politeness strategy data, 2 bald on record data, and 1 off record data. In his role as President, Joe Biden understands or acknowledges that the people who come to see him at that address are the ones who support him. And he is trying to protect his people by guaranteeing their safety during the Ukrainian-Russian war and making a better world in the future after the pandemic. That is why he mostly uses positive politeness strategies. Moreover, Joe Biden only uses 1 data of off-record politeness strategy data because he wants to show his strength in leading the country.